Strategies to improve adherence to antiretroviral therapy and retention in care for people living with HIV in high-income countries: a protocol for an overview of systematic reviews. Issue 9 (11th September 2018) - Mbuagbaw, Lawrence; Mertz, Dominik; Lawson, Daeria O; Smieja, Marek; Benoit, Anita C; Alvarez, Elizabeth; Puchalski Ritchie, Lisa; Rachlis, Beth; Logie, Carmen; Husbands, Winston; Margolese, Shari; Thabane, Lehana
Abstract : Introduction: While access to antiretroviral therapy (ART) for people living with HIV has expanded in recent years, additional efforts are required to support adherence to medication and retention in care. Interventions should be applicable in real-world settings and amenable to widespread use. The objectives of this overview are to identify effective pragmatic interventions that increase adherence to ART and retention in care for people living with HIV at high risk for suboptimal adherence and retention in high-income countries. Methods and analysis: We will conduct an overview of systematic reviews of studies on interventions which target improved adherence to medication and retention in care among high-risk people living with HIV in high-income countries (men who have sex with men, African, Caribbean and black people, sex workers, people who inject drugs, indigenous people and other socially marginalised groups). We will search the following databases: PubMed, EMBASE (Exerpta Medica Database), CINAHL (Cumulative Index to Nursing and Allied Health Literature), PsycINFO, Web of Science and the Cochrane Library. We will conduct screening, data extraction and assessment of methodological quality of the systematic reviews. Analysis will be narrative. Our findings will be interpreted in light of the certainty of the evidence, level of pragmatism, setting and population of interest. Ethics and dissemination: Only published secondary data will be used in this study, and therefore ethics approval is not required. Our findings will be disseminated as peer-reviewed manuscripts, conference abstracts and through community activities. The findings from this overview will inform a mixed-methods study among people living with HIV and health workers in Ontario, Canada.